The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.5380/reterm.v5i1.61665
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Partial Oxidation of Methane in a Membrane Reactor

Abstract: Partial oxidation of methane is one of the most important chemical processes for the production of syngas. In recent years, the abundant availability of natural gas and the increasing demand of hydrogen have led to high interest to further develop this process increasing the yield of syngas. In this work the partial oxidation of methane was studied from a modeling point of view in a membrane reactor and in a conventional reactor. A mathematical model of a membrane reactor used for partial oxidation of methane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This ratio is very important for the quality of the syngas used as a feedstock for the gas to liquid processes (GTL). The recommended optimum value of this ratio lies between 0.7 up to 3.0 . It is shown that the profiles assume inflection points as a reflection to the behavior of the H 2 and CO profiles shown in Figures a and a, respectively.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This ratio is very important for the quality of the syngas used as a feedstock for the gas to liquid processes (GTL). The recommended optimum value of this ratio lies between 0.7 up to 3.0 . It is shown that the profiles assume inflection points as a reflection to the behavior of the H 2 and CO profiles shown in Figures a and a, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…Iron and Cobalt based catalysts are used in industry to catalyze Fishcer–Tropsch synethsis. Low-temperature Fischer–Tropsch (LTFT) and high-temperature Fischer–Tropsch (HTFT) processes are used to produce different products such as gasoline, diesel oil, linear olefins, and waxy material. Depending on the target product, catalyst, and operating conditions, the ratio of H 2 /CO in Fishcer–Tropsch synthesis can be adjusted accordingly. In order to ensure that the appropriate industrial range is satisfied to any desired level, it is possible to adjust this ratio by mixing part of the pure hydrogen with the syngas from the CFFBMR 2 as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The products obtained as a result of reaction (1) upon contact with the active centers of the catalyst and methane molecules interact according to the following reactions [ 28 ] CO 2 + CH 4 = 2CO + 2H 2 H 2 O + CH 4 = CO + 3H 2 …”
Section: Methodsmentioning
confidence: 99%
“…The processes have been simulated with the open-source process simulator DWSIM [ 36 ]. In addition, the mathematical software MATLAB was used to check the evolution of the different kinetics of each process (which were compiled from different previous articles): natural gas pyrolysis [ 37 ], dry reforming of methane [ 37 ], steam reforming of methane [ 38 ], partial oxidation of methane [ 39 , 40 ], electrolysis [ 41 ], coal gasification [ 42 , 43 ] and autothermal reforming of methane [ 44 ]. This information is detailed in “ supplementary materials ”.…”
Section: Methodsmentioning
confidence: 99%